Food intake, nutrient utilization and water turnover in the lesser mouse-deer (Tragulus javanicus) given lundai (Sapium baccatum) - Nolan, J.V.; Liang, J.B.; Abdullah, N.; Kudo, H.; Ismail, H.; Ho, Y.W.; Jalaludin, S. (Elsevier, 1995)
Voluntary food intake, digestibility and water turnover were determined in adult Malaysian lesser mouse-deer (Tragulus javanicus) given unlimited access to lundai foliage (Sapium baccatum). Daily dry matter (DM) intake was 42.4 g/kg metabolic live mass (M0.73) or 3.7% M. Digestible energy intake was 853 kJ/day (571 kJ metabolisable energy per M0.73), calculated to be used with 79% efficiency. Apparent digestibility (%) of organic matter was 83.8, crude fibre 63.7, acid detergent fibre 60.5, neutral detergent fibre 72.1 and crude protein 65.0. Urinary excretion of the purine derivative, allantoin, was 0.05 mg/g digestible DM intake suggesting rumen microbial yield efficiency may be lower than in other ruminant species. Total water intake was 182 ml/M0.82. The body-water content of the fed mouse-deer, from tritiated water dilution, was 77% M, consistent with a very lean carcass. Turnover of body water was 17% per day. The mouse-deer produced relatively dry, well-defined faecal pellets.